2007
DOI: 10.1158/0008-5472.can-06-4076
|View full text |Cite
|
Sign up to set email alerts
|

A Gynecologic Oncology Group Study of Platinum-DNA Adducts and Excision Repair Cross-Complementation Group 1 Expression in Optimal, Stage III Epithelial Ovarian Cancer Treated with Platinum-Taxane Chemotherapy

Abstract: To determine whether platinum-DNA adducts and/or mRNA expression of the excision nuclease excision repair crosscomplementation group 1 (ERCC1) from peripheral blood leukocytes (PBL) were associated with clinical outcome in women with epithelial ovarian cancer (EOC), participants that had previously untreated, optimally resected, stage III EOC were randomized to paclitaxel plus cisplatin or carboplatin. DNA and RNA were extracted from PBLs collected 20 to 28 h post-drug infusion. DNA adducts were measured by at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
2
26
0
1
Order By: Relevance
“…In epithelial ovarian cancer, Darcy et al (2007) analyzed whether mRNA expression of ERCC1 in PBLs was associated with clinical outcomes in patients treated with platinum-taxane chemotherapy, although negative results were reported. Herein, we assessed correlations between expression of ERCC1 in PBLs and outcomes in 48 gastric cancer patients treated with oxaliplatin-based adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In epithelial ovarian cancer, Darcy et al (2007) analyzed whether mRNA expression of ERCC1 in PBLs was associated with clinical outcomes in patients treated with platinum-taxane chemotherapy, although negative results were reported. Herein, we assessed correlations between expression of ERCC1 in PBLs and outcomes in 48 gastric cancer patients treated with oxaliplatin-based adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Low ERCC1 protein expression was related to improved outcomes for adjuvant platinum-based chemotherapies in non-smallcell lung cancer (NSCLC) patients (10). Other studies have shown a correlation between increased gene and/or protein ERCC1 expression and unresponsiveness and/or decreased survival after platinum-based chemotherapy in different tumor types (11)(12)(13)(14). However, a high ERCC1 level might also be a positive prognostic variable because it may increase the removal of carcinogenic DNA lesions.…”
Section: Introductionmentioning
confidence: 99%
“…More recently in a study involving over 700 completely resected tumors from patients with non-small-cell lung cancer, a signifi cant survival benefi t from cisplatin-based adjuvant chemotherapy compared to observation was associated with the absence of ERCC1 protein as assessed by immunohistochemistry (8). However, a prospective study in 170 patients with previously untreated ovarian cancer evaluating ERCC1 mRNA in peripheral blood leukocytes as a tumor surrogate, found no correlation with any clinical endpoint measured after receiving platinum-based chemotherapy (9). Finally, a genetic polymorphism in ERCC1 (codon 118 C to T) resulting in decreased ERCC1 protein levels has been associated with platinum sensitivity and higher response rates in colon and ovarian cancer (10).…”
Section: Clinical and Translational Leadsmentioning
confidence: 99%